WACANA RASIALISME DALAM SOSIOLOGI MAX WEBER - Haryono, Satrio Dwi (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
Sociology is a science that studies human relations with humans. Sociology as a science that studies humans emerged later than other sciences. Max Weber as a western sociologist who has studied the eastern world as the object of his study is considered to have a lot of ethnocentric content, namely eurocentric. This has implications for the creation of a reflection of Europe, namely the east, which Weber describes eloquently. Although at first Weber tried to explain the process of change in Western Europe, but it became an object of studying the east as the other or the other of Europe. As a methodological tool, the author uses library research. In this study, the writer finds a number of identifications of entocentrism in Max Weber's sociology in primary and secondary sources. The results of this study indicate that the ethnocentrism attributed to Europe which in the course of history will lead to major problems that Weber did not calculate, such as colonialism and imperialism.